PENYIMPANGAN AJARAN MA'HAD AL-ZAYTUN TERHADAP HUKUM ISLAM - Muhammad Iklil Musyafa; Novita Sari Ramadhani; Sadam Dzul Fahmi (Pusat Riset dan Inovasi Nasional, 2023)
This paper explains the Deviations of Ma'had Al-Zaytun's Teachings Against Islamic Law, where the activity is in a ma'had or pondok in Indramayu, Central Java. During the leadership of Prof. Dr. KH. Abdusallam Rasyidi Panji Gumilang has recently reaped a lot of controversy because the teachings applied at the education center are contrary to Islamic religious laws or teachings, such as the prayer rows that are spaced apart and the mixing of male and female rows, Hajj can be carried out in Indramayu, adheres to Bung Karno's and Ma'had's understandings also say that sins can be redeemed with money. It also describes rebuttals regarding teachings in Al-Zaytun which are considered deviant and far from Islamic values ​​and law. to discuss related to deviant teachings in ma'had Al-Zaytun that are contrary to Islamic religious law, and the author will also look for what are the factors that underlie the ma'had carrying out teachings that are not in accordance with religious law or Islamic Shari'a which should.